2019
DOI: 10.1093/pm/pnz030
|View full text |Cite
|
Sign up to set email alerts
|

Direct Health Care Cost and Work Incapacity Related to Complex Regional Pain Syndrome in Switzerland: A Retrospective Analysis from 2008 to 2015

Abstract: Objective First, to determine the number of accident-related complex regional pain syndrome (CRPS) cases from 2008 to 2015 and to identify factors associated with an increased risk for developing CRPS. Second, to analyze the duration of work incapacity and direct health care costs over follow-up periods of two and five years, respectively. Design Retrospective data analysis. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 17 publications
2
30
0
1
Order By: Relevance
“…This survey provides support for health care resources to be directed towards the early diagnosis and intervention of CRPS. This is further supported by a recent retrospective analysis conducted in a Swiss post‐accident population, which reported that average treatment costs, after an accident resulting in CRPS, were 13 times higher, and the number of days lost at work were 20 times higher, than those in patients without CPRS (Scholz‐Odermatt et al, ).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This survey provides support for health care resources to be directed towards the early diagnosis and intervention of CRPS. This is further supported by a recent retrospective analysis conducted in a Swiss post‐accident population, which reported that average treatment costs, after an accident resulting in CRPS, were 13 times higher, and the number of days lost at work were 20 times higher, than those in patients without CPRS (Scholz‐Odermatt et al, ).…”
Section: Discussionmentioning
confidence: 65%
“…Health care systems have many competing demands. Despite being a relatively rare condition, CRPS is associated with significant economic consequences (Kemler, Raphael, Bentley, & Taylor, ; Scholz‐Odermatt, Luthi, Wertli, & Brunner, ). This survey provides support for health care resources to be directed towards the early diagnosis and intervention of CRPS.…”
Section: Discussionmentioning
confidence: 99%
“…Although many cases will resolve within 6 to 13 months, a recent systematic review found that between 22 and 64% of patients experience persistent symptoms ≥3 years after diagnosis [20] and, as a consequence, CRPS has a significant impact on the health economy and health-related quality of life [21]. A recent retrospective analysis of the Swiss National Accident Insurance database reported high economic costs associated with CRPS [22]. Average treatment costs were found to be 13 times greater, and the number of working days lost was 20 times higher, in patients with CRPS after an accident, compared with those without CRPS [22].…”
Section: Vasomotormentioning
confidence: 99%
“…3 Because the optimal treatment for a DRF remains an ongoing discussion and the duration of immobilization is still a subject of debate, this study observed whether early activity postinjury can lead to prevention of type 1 complex regional pain syndrome (CRPS-1), [4][5][6][7] a syndrome that can lead to high health care costs and inability to work. 8 Type 1 complex regional pain syndrome is described as a posttraumatic pain syndrome combined with an autonomic disorder and includes excessive pain, edema, changes in skin blood flow, abnormal sudomotor activity, sensory and motor disturbances and severe disability leading to mood changes, loss of work capacity, and decreased participation in recreational activities. 9,10 The diagnosis is based on a combination of symptoms reported by the patients and signs observed during physical examination by the physician.…”
Section: Introductionmentioning
confidence: 99%